2006
DOI: 10.1111/j.1528-1167.2006.00899.x
|View full text |Cite
|
Sign up to set email alerts
|

Regional Cerebral Blood Flow and Developmental Outcome in Cryptogenic West Syndrome

Abstract: Summary:Purpose: To elucidate the relation between alterations of regional cerebral blood flow (rCBF) by adrenocorticotropic hormone (ACTH) therapy and developmental outcomes of cryptogenic West syndrome.Methods: Quantitative measurement of rCBF, with autoradiography method using N-isopropyl-( 123 I) p-iodoamphetamine single photon emission computed tomography before and after ACTH therapy, was performed on 17 infants with cryptogenic West syndrome. Regions of interest for rCBF were placed bilaterally in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Other investigators have confirmed these results by using SPECT or PET. 10,11 In all of the previous studies, the follow-up period was limited to a minimum of 2 or 3 years, and educational outcome was not reported. Although gross motor development or simple language development can be evaluated by 2 or 3 years of age, evaluation at this age is not sufficient for higher cognitive functioning or socioeducational status.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other investigators have confirmed these results by using SPECT or PET. 10,11 In all of the previous studies, the follow-up period was limited to a minimum of 2 or 3 years, and educational outcome was not reported. Although gross motor development or simple language development can be evaluated by 2 or 3 years of age, evaluation at this age is not sufficient for higher cognitive functioning or socioeducational status.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have reported PET hypometabolism or SPECT hypoperfusion during the early stage of cryptogenic West syndrome. [6][7][8][9][10][11] We also have reported evolutional changes in cortical hypometabolism on PET and have suggested the usefulness of PET for predicting the prognosis. [6][7][8][9] The results of our studies and others revealed that persistent hypometabolism or hypoperfusion after initial pharmacologic treatment suggests poor developmental outcome.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The following conclusions probably give a fair account of the overall prognosis irrespective of cause. 22,43,52,[69][70][71][72][73][74][75][76][77] Mortality has fallen to about 5% in developed countries because of improved medical care. Deaths may be due to the underlying cause and treatment mainly with ACTH and corticosteroids.…”
Section: Prognosismentioning
confidence: 99%
“…2 We and others have reported hypometabolism on PET and hypoperfusion on SPECT during the early stages of cryptogenic WS. [3][4][5][6][7][8][9] Detecting these findings is useful for both predicting long-term outcomes and detecting underlying lesions. [3][4][5][6]8,9 Further progress of modern neuroimaging techniques is expected to clarify the underlying pathology in patients with WS of unknown etiology.…”
mentioning
confidence: 99%